Tratamento da ectopia do epitélio colunar do colo do útero com acupuntura sistêmica e análise dos fatores de interferência no processo metaplásico - Fernandes, Silvana Maria Silva [UNIFESP] (2017)
Objective: To evaluate acupuncture as a treatment for uterine cervical ectopy with analysis of risk factors that interfere with the metaplastic response. Specific objectives are to confirm the syndromic model used in the previous selection of acupuncture points; to compare conventional cytology Pap smear (CPS) versus Liquid-based cytology (LBC); to verify the incidence of high-risk Human Papillomavirus (HPV-HR), its relationship with ectopy size and metaplastic response; demonstrate the use of computerized planimetry. Methods: We selected 51 women with ectopy, without previous therapy, negative CPS and without signs suggestive of the HPV-induced effect, in Study group (S), treated with 10 sessions of acupuncture, weekly and Control group (C) under expectant management. The Ethics and Research Committee approved the project, and we offer a free and informed consent form. After anamnesis, we collected samples for LBC and DNA HPV-HR research and colposcopy with photograph, repeated at 90 days’ follow-up. We evaluated the therapeutic response, using planimetry, considering the differential of the percentages of the areas of ectopy (ΔPe). The data were analyzed statistically. Results: Study group had 23 women and C group had 28, mostly Caucasian, symptomatic and non-smokers. The mean age was 25.6 years. Group S had a higher mean age (p= 0.040), higher age of first sexual intercourse (p<0.001), longer time interval between menarche and first sexual intercourse (p<0.001) and used less hormonal contraceptive (HC) (p<0.001). Regarding age of menarche, number of sexual partners, sexual frequency/month and results of CPS and LBC, there was no difference between groups. Study group presented higher ΔPe than C (p<0.001). We confirmed the Internal Heat Syndrome Deficient of Yin and QI. HPV OT predominated in women younger than 25 years, unrelated to ectopy size and ΔPe. The use of HC had a relation with lower ΔPe (p= 0.006). Conclusion: Study group, treated with acupuncture, had a greater reduction of ΔPe and a probable stimulus to epithelialization. The pathophysiological model of ectopy, according to TCM, was confirmed. CPS confirmed the LBC. Prevalence of HPV OT in women younger than 25 years. The use of HC was associated with lower ΔPe. Planimetry proved to be appropriate, practical, and replicable.